Label‐free optical detection of cyclosporine in biological fluids. Issue 4 (13th December 2018) - Marzejon, Marcin; Kosowska, Monika; Majchrowicz, Daria; Bułło‐Piontecka, Barbara; Wąsowicz, Michał; Jędrzejewska‐Szczerska, Małgorzata
Abstract: In this paper, a spectroscopic method for determination of cyclosporine concentrations in biological fluids is presented. Blood plasma and hemoglobin solutions are chosen for the experiment. For various cyclosporine concentrations in blood plasma and hemoglobin, absorbance measurements in spectra range from 600 to 1100 nm are performed. The measurement results are analyzed by the use of a dedicated algorithm. The obtained data are characterized by a high coefficient of correlation R 2, which is equal to 0.9461 and 0.9808 for blood plasma and hemoglobin, respectively. The proposed method enables the selective detection of cyclosporine level and could be applied in medicine and laboratory diagnostics. The obtained result can be the base to build the point‐of‐care CsA level detection optical sensor. Abstract : The label‐free optical method for detection of immunosuppressive drug in biofluids is described. Several solutions varying in cyclosporine level in blood plasma and in hemoglobin are prepared and investigated. The measurements of absorbance are carried out with commercially available spectrophotometer in the spectra range 600 ÷ 1100 nm. The direct correlation between measured absorbance and cyclosporine level in prepared samples is found.